Impact of Cordyceps sinensis on coronary computed tomography angiography image quality and renal function in a beagle model of renal impairment - Song, Peiji; Li, Kun; Xu, Xiaodie; Zhang, Guifeng; Wang, Zengkun; Sun, Linbing; Zhao, Zekai; Li, Ting; Wang, Ximing; Xia, Zhangyong (Frontiers in Pharmacology, 2025)
ObjectiveThis study aims to investigate the protective effects of Cordyceps sinensis against renal injury induced by low-dose contrast medium (CM) in coronary computed tomography angiography (CCTA) imaging, and to evaluate its efficacy using functional magnetic resonance imaging (fMRI).MethodsTwenty Beagle dogs with induced renal insufficiency were enrolled in the study and randomly assigned to one of four groups (n = 5 per group). Group A received Cordyceps sinensis for 1 week prior to undergoing heart rate-dependent personalized CM CCTA scanning; Group B received Cordyceps sinensis for 1 week followed by conventional dose CM CCTA scanning; Group C did not receive Cordyceps sinensis but underwent HR-dependent CM CCTA scanning; and Group D did not receive Cordyceps sinensis but underwent conventional dose CM CCTA scanning. Renal function was assessed using MRI before and after the intervention, with IVIM (Intravoxel Incoherent Motion) and BOLD (Blood Oxygen Level Dependent) imaging of the kidneys. Key parameters, including the pure diffusion coefficient (D), pseudo-diffusion coefficient (D*), perfusion fraction (f), and R2*values, were quantified. Laboratory renal function markers were measured multiple times before and after the intervention, and their correlation with fMRI parameters was analyzed.ResultsCCTA imaging revealed that the CT values of the major coronary artery branches in all groups met the international diagnostic criteria for coronary arteries. No statistically significant differences in image quality were observed among the four groups (P > 0.05). In Groups A and D, significant changes were observed in renal function parameters, as well as in D, D*, f, and R2* values, both pre- and post-CCTA (P < 0.05). However, Groups B and C exhibited no significant changes pre- and post-CCTA (P > 0.05). A significant correlation was found between MRI parameters and laboratory renal function markers, with excellent inter- and intra-observer reproducibility, and high repeatability in the measurements.ConclusionHR-dependent personalized CM CCTA imaging did not compromise image quality. Administration of Cordyceps sinensis demonstrated a potential protective effect on renal function. The combination of IVIM and BOLD functional MRI offers a reliable, non-invasive approach to assess the protective effects of Cordyceps sinensis on renal injury induced by low-dose CCTA in Beagle dogs.